Let justice descend - Black, Lisa, 1963- (Black, Lisa, 1963- Gardiner and Renner thriller., 2019)
Three days before a key election, U.S. Senator Diane Cragin is electrocuted on her own doorstep<U+2014>a shocking twist in an already brutal political race. Cragin<U+2019>s chief of staff is quick to blame rival Joey Green, a city development director who<U+2019>s had his hand in every till in town for over twenty years. Maggie and Jack have their own theories, especially after discovering a fortune in cash in the senator<U+2019>s safe. But as they follow the money through the treacherous landscape of Cleveland politics, they find many more millions in play<U+2014>and more suspects. As Jack says, “Anyone can be dangerous, when they have what they think is a good reason.” He should know. Now a Herald reporter is perilously close to discovering the truth about Jack<U+2019>s penchant for acting as both detective and executioner. With each passing hour, the stresses of the impending election expose new fractures and corruption at the city<U+2019>s highest levels. And as one murder leads to another, and another, Maggie and Jack<U+2019>s only hope of stopping a killer is an alliance that<U+2019>s growing ever more fragile.